A Multi-disciplinary and Comparative Approach to Evaluating Pre-trial Detention Decisions: Towards Evidence-Based Reform - Dhami, Mandeep K. (European journal on criminal policy and research, 2022)
The decision to remand a defendant into custody pre-trial is one of the most controversial criminal justice decisions because it deprives individuals of their liberty while they are presumed to be innocent of a crime. Indeed, pre-trial detention decisions can have significant consequences for defendants, which need to be balanced against the potential implications of bail for public safety and the course of criminal proceedings. Despite this, court-based bail and remand decision-making remains relatively underexplored. In this paper, we compare court-based bail/remand decision-making in England and Wales and The Netherlands. We focus on (i) the procedure and structure of decision-making, (ii) the substantive relevant legal frameworks, (iii) the courts in which the decisions are made and the decision-makers in those courts, (iv) the conditions characterizing the decision task, and (v) the court’s reasoning of bail and remand in custody decisions. Using a comparative and multi-disciplinary approach, relying on Law, Criminology, and Psychology, we make predictions about bail and remand in custody rates in the two jurisdictions as well as the decision performance of court-based decision-makers. These predictions are then evaluated using available (official) statistics and past research. We identify the need to collect more nuanced statistical data on bail and remand in custody rates and point to potentially fruitful avenues for future research. A comparative, multi-disciplinary, evidence-based approach can underpin remand reform in England and Wales, The Netherlands, and beyond.